2019
DOI: 10.1159/000504366
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Safety of Epicutaneous Immunotherapy for Allergic Diseases: A Systematic Review and Meta-Analysis

Abstract: <b><i>Objectives:</i></b> To systematically review the effect and safety of epicutaneous immunotherapy (EPIT) for allergic diseases. <b><i>Methods:</i></b> We searched PubMed, EMBASE, Cochrane Central Register of Controlled Trials, China National Knowledge Infrastructure, CQ VIP Database, Wanfang Data, and international trial register from their inception to July 29, 2019, without language restrictions, for randomized controlled trials (RCTs) that compared EPIT v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 34 publications
0
25
0
2
Order By: Relevance
“…91,92 An overview of experience gained in EPIT trials is summarized in a very recent review article. 93 This review concludes that "EPIT might induce desensitization in peanut allergy and an increased risk of local adverse events (AEs). These findings should be interpreted with caution owing to the limited study and heterogeneity.…”
Section: Epicutaneous Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…91,92 An overview of experience gained in EPIT trials is summarized in a very recent review article. 93 This review concludes that "EPIT might induce desensitization in peanut allergy and an increased risk of local adverse events (AEs). These findings should be interpreted with caution owing to the limited study and heterogeneity.…”
Section: Epicutaneous Immunotherapymentioning
confidence: 99%
“…More than 10 years ago the first studies appeared, suggesting epicutaneous allergen administration for epicutaneous immunotherapy (EPIT) 91,92 . An overview of experience gained in EPIT trials is summarized in a very recent review article 93 . This review concludes that “EPIT might induce desensitization in peanut allergy and an increased risk of local adverse events (AEs).…”
Section: Current Situation Of Aitmentioning
confidence: 99%
“…Data from epicutaneous AIT (EPIT) studies performed with peanut allergen extracts provide evidence for clinical effects [ 37 ▪▪ , 38 ▪▪ ] (Table 1 ) but these effects are modest, and a systematic review and metaanalysis [ 39 ] concludes that more studies are necessary to understand if this form of AIT is effective. Furthermore, the mechanisms of EPIT are not clear as it has been demonstrated that epicutaneous allergen administration induces no relevant increases of allergen-specific IgG antibodies but rather increases allergen-specific T-cell activation [ 40 ].…”
Section: Allergen Extract-based Allergen-specific Immunothementioning
confidence: 99%
“…Epicutaneous immunotherapy (EPIT) is a more recent approach which has been developed originally for AIT of respiratory allergy ( 288 ) but has now been evaluated also for AIT of peanut allergy ( 235 , 289 ). EPIT is based on the direct application of an allergen-containing patch on the patient´s skin, similar as it is performed in APT.…”
Section: Allergen-specific Immunotherapies For Nut Allergiesmentioning
confidence: 99%
“…These findings should be interpreted with caution owing to the limited study and heterogeneity. More data in the older (children ≥ 12 years and adults) and other allergic diseases are needed” ( 289 ). The analysis of systemic peanut allergen-specific IgG responses has shown that epicutaneous allergen administration induces only a very modest production of allergen-specific IgG and mainly specific T cell activation ( 16 ).…”
Section: Allergen-specific Immunotherapies For Nut Allergiesmentioning
confidence: 99%